Digital Labour Platformer’s Legal Status and Decent Working Conditions: European Union and Indonesian Perspective - Rahman, Rofi Aulia; Hajdú, József; Nathanael, Valentino (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
This article aims to provide the recent court decision on legal status and working conditions for the gig worker in European Union as well as a lesson for Indonesia through the EU’s notion on gig workers. The European Union (EU) Commission enacted in 2021 a draft Directive proposal to ensure Europe's gig (platform) workers enjoy the same labour rights as other traditional employees. This article employs doctrinal legal research with statutory and comparative approach, as well as court decision are considered as the main basis to protect gig workers. The result shows that the drafts Directive to ensure Europe’s gig workers is relied on Articles 16 and 153 (1)(b) of the Treaty on the Functioning of the EU (TFEU), on data protection and working conditions, respectively. It has the advantage of giving certainty about the minimum requirements and procedural obligations that Member States must apply in platform work relations. Courts of several EU MSs, including Belgium, France, Greece, Italy, the Netherlands, Portugal, Spain, and the UK, already ruled in favour of platform workers not qualifying as self-employed, obliging platforms to reclassify them as employees. Meanwhile, Indonesia's perspective on gig workers remains vague, and the minimal standards for gig workers are unbalanced in comparison to the EU's perspective on gig workers. This article introduces the main notions and provisions of the proposed EU platform work Directive and analyses the current conditions and legal framework of Indonesia in handling the issue of gig workers.